Paura e sottrazione dal mondo. Una lettura di "Persona" di Ingmar Bergman - Dal Sasso, Davide (Filosofia, 2016)
The main aim of this essay is to examine the relationship between fear and the urge to escape from the world. This impulse reveals the basic connection between fear and sensitivity, and turns into an attempt to elude the relationship and the encounter with the world and individuals. This attempt has two main features: on the one hand, it can be thought of as a sign of the deep bond between two dimensions, private and public, in which fear can manifest. On the other hand, it refers primarily to a significant condition that is articulated into the stages of apprehension, uncertainty in relation to the acknowledgment of the others, and the possibility that fear may coincide with the angst. In the following pages I investigate these stages of anticipation of fear in relation to the attempt to elude the world, by taking as main reference a film of Ingmar Bergman, Persona.